Inovasi Produk Dan Digitalisasi Layanan Pada Pegadaian Syariah Di Era Ekonomi Digital: Introduction, Research Method, Study Theory, Research Results and Discussion, Conclusion - Fitroh Nurhayati; Lovi Yandi; Najwa Syifa Quthunnadaa Sausan; Anas Malik (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the effectiveness of product innovation and service digitalization at Pegadaian Syariah in increasing financial inclusion in the digital economy era. The research method used is descriptive qualitative with data collection techniques through in-depth interviews, participatory observation, and documentation of Pegadaian Syariah employees and customers. The results of the study indicate that digital transformation, through the development of the Pegadaian Syariah Digital (PSD) application and modernization of technological infrastructure, is able to increase transaction efficiency, expand service coverage, and support sharia financial inclusion. However, the main challenges faced include the digital literacy gap, data security risks, and the complexity of multi-sharia contracts. This study recommends a hybrid strategy of offline-online services and an adaptive contract model so that services are more inclusive and easily accessible to all levels of society, while still being based on sharia principles.